2004
DOI: 10.1158/1078-0432.ccr-03-0422
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Flavopiridol in Human Neuroblastoma Cells Is Enhanced under Hypoxia and Associated With N-myc Proto-oncogene Down-Regulation

Abstract: Purpose: Neuroblastoma is the most common extracranial solid tumor of children that arises from the sympathetic nervous system. Survival rates for neuroblastoma patients is low despite intensive therapeutic intervention, and the identification of new effective drugs remains a primary goal. The cyclin-dependent kinase inhibitor, flavopiridol, has demonstrated growth-inhibitory and cytotoxic activity against various tumor types. Our aim was to investigate flavopiridol effects on advanced-stage, N-myc proto-oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…4 On the contrary, our experiments using primary CLL tumor cells suggest that since flavopiridol-induced loss of ⌬⌿ m is not rescued by either a pan-caspase inhibitor or specific inhibitors of caspase-8 and caspase-9, this process is either caspase-independent or lies upstream of caspase activation. Furthermore, Puppo et al 43 showed that treatment of human neuroblastoma cells with flavopiridol causes an early activation of caspase-3 prior to extensive cell death, similar to what we reported previously in CLL patient cells. 44 However, in this report, caspase-8 and caspase-9 were not activated, suggesting that in flavopiridol-mediated cytotoxicity caspase-3 may be acting upstream of these activator caspases.…”
Section: Discussionsupporting
confidence: 88%
“…4 On the contrary, our experiments using primary CLL tumor cells suggest that since flavopiridol-induced loss of ⌬⌿ m is not rescued by either a pan-caspase inhibitor or specific inhibitors of caspase-8 and caspase-9, this process is either caspase-independent or lies upstream of caspase activation. Furthermore, Puppo et al 43 showed that treatment of human neuroblastoma cells with flavopiridol causes an early activation of caspase-3 prior to extensive cell death, similar to what we reported previously in CLL patient cells. 44 However, in this report, caspase-8 and caspase-9 were not activated, suggesting that in flavopiridol-mediated cytotoxicity caspase-3 may be acting upstream of these activator caspases.…”
Section: Discussionsupporting
confidence: 88%
“…Hypoxic conditions (0.1% O 2 ) were achieved by culturing the cells in an anaerobic workstation incubator (Concept 400, Jouan, Milan, Italy) flushed with a gas mixture containing 0.1% O 2 , 5% CO 2 , and balanced N 2 at 37jC in a humidified atmosphere (10). Oxygen tension in the medium was measured with a portable trace oxygen analyzer (Dräger PACIII).…”
Section: Methodsmentioning
confidence: 99%
“…Accumulation of HIF-1α and/or HIF-2α proteins has been observed in vitro in various advanced-stage, metastatic human neuroblastoma cell lines exposed to hypoxia [28]. Hypoxia has a profound impact on aggressive neuroblastoma behavior: increased production of the vascular endothelial growth factor (VEGF), inhibitor of differentiation (ID), and Notch family proteins was observed in hypoxic neuroblastoma cells both in vitro and in vivo [29,30]. Interestingly, high levels of HIF-2α expression have been proposed to promote an aggressive neuroblastoma phenotype [21].…”
Section: (3) Hif-2α In Neuroblastomamentioning
confidence: 99%